A case study of public relations and marketing practices in the Rizal Provincial Library - Soliman, Andrei C. (School of Library and Information Studies, University of the Philippines Diliman, 2009)
Public libraries today are faced with a tough challenge of continuing to provide solutions to the information needs of people amid heavy competition. The competition arises from the ever increasing developments in technology like faster and more portable computers and readily available Internet access almost everywhere. The dwindling number of visitors in most public libraries in the Philippines is surely a matter of great concern and that is why librarians must be able to adapt to these different changes and use it for the benefit of the library and its clients.